A Printed and Flexible NO2 Sensor Based on a Solid Polymer Electrolyte - Luo, Ru-bai; Li, Hai-bin; Du, Bin; Zhou, Shi-sheng; Chen, Yu-heng (Frontiers in Chemistry, 2019)
Solid polymer electrolyte (SPE) is an important part of printed electrochemical gas sensors and are of value to electrochemical sensors. Here, a new type of SPE was prepared by dissolving a poly-vinylidene fluoride (PVDF) matrix in a 1-methyl-2-pyrrolidone (NMP) to immobilize 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM] [BF4]), which was then used in a new electrochemical amperometric nitrogen dioxide sensor. The SPE was coated on a single electrode and attached to the electrode to construct a simple two-layer structure. Nitrogen dioxide in the air was reduced on the working electrode at a bias voltage of −500 V. We controlled the components and process parameters separately for control experiments. The results show that the SPE based on [EMIM] [BF4], NMP, and PVDF coated on the electrode at a thickness of 1.25 mm with a 1:1:4 weight ratio under heat treatment conditions of 80°C for 2 min has the best sensitivity. The FTIR and XPS results indicated that SPE is prepared via physical miscibility. The SEM and XRD results showed that the sensitivity of the sensor is strongly dependent on the interconnected pore structure in SPE, and the pore structure is related to the synthesis ratio, morphology, and heat treatment mode of SPE. Moreover, the sensor sensitivity has a certain relationship with SPE conductivity. The reaction principle and cycle performance of the sensor were also studied.